LESSON 1. The Criminal behaviour as action or omission. Exclusion from action or omission. - Fernández-Díaz, Carmen Rocío (Aranzadi, 2020)
The human behaviour that a person materializes in the outside world constitutes the core of the offence, resulting in the violation of a criminal legal norm. It therefore follows that, although natural phenomena (storm, hurricane, fire, flood…), or animals themselves, can also produce harmful results (damage to things or injuries or death to people), only human beings can commit criminal acts. If an animal bites a person, the consequent injuries cannot serve as the basis for a crime of injury. Such an attack could only be considered «criminal» if the animal had been flogged by a person or if the attack was a resultant of a lack of care on the part of the owner. In both cases, the criminally relevant behaviour would be that of the owner rather than that of the animal.
Keywords: Derecho penal; Delitos; Action; Omission; Human behaviour; Criminal law